Physical activity and diet in a global pandemic: an investigation of the impact of COVID-19 on factors relevant for musculoskeletal health at two different stages of the lifecourse - Bevilacqua, G; D'Angelo, S; Linaker, C; Paul, A; Bloom, I; Zhang, J; Laskou, F; Cooper, C; Ward, KA; Walker-Bone, K; Dennison, EM (Frontiers Media, 2022)
Background: Physical activity, nutrition and other lifestyle factors play important roles in maintaining musculoskeletal health. The coronavirus disease (COVID-19) originated in late 2019, spread globally to be declared a pandemic by the World Health Organisation in March 2020, and led to widespread behaviour change. The aim of this study was to use two existing cohorts, the Hertfordshire Cohort Study (HCS) and Health and Employment After Fifty Study (HEAF), to understand how wave one of the COVID-19 pandemic impacted lifestyle factors associated with musculoskeletal health in the UK.